Transformational Leadership and Work Engagement on Organizational Citizenship Behavior With Learning Organization as A Mediation Variable - Soilihin, Agung; Fathihani (Dinasti International Journal of Management Science, 2024)
This study aims to find out that Leadership Leadership in Work Engagement has an influence on Organizational Citizenship Behavior in Leadership Leadership mediates the influence of Leadership Leadership and Work Engagement on Organizational Citizenship Behavior. The population used is employees of PT. Penida Kreasi Persada with a sample of 85 employees. Data collection was carried out using a questionnaire method where respondents answered questions arranged in choice form and the question scale used a Likert scale (1-5). The method used in this research is quantitative analysis with the SEM analysis tool and the SmartPLS 3.3 tool. The research results show that Transformational Leadership is positive and has no significant effect on Organizational Citizenship Behavior. Work engagement has a significant positive effect on Organizational Citizenship Behavior. Transformational Leadership and Work Engagement have a significant positive effect on learning organizations. Learning organization has a significant positive effect on Organizational Citizenship Behavior. Transformational leadership and work engagement have a significant positive effect on organizational citizenship behavior through learning organizations.